The Role of Brand Equity and Perceived Value on Student Loyalty: A Case Study of Private Universities in Indonesia - Rolando, Benediktus; Mulyono, herry; Pasaribu, Johni Paul Karolus (LPPM Universitas Dinamika Bangsa, 2024)
With the growing importance of customer loyalty, there is still confusion about what can influence and improve loyalty in the education sector. Although research on the topic of customer loyalty is vast and growing, not much literature focuses on students and people in the education sector. In the absence of such consensus, the purpose of this study is to examine how perceived value and brand equity influence student satisfaction and loyalty, specifically in the setting of the Private Higher education sector. The data collection method was obtained from 200 samples of university students in Jambi (primary data) using Structural Equation Model AMOS 26 analysis: four hypotheses have a positive and significant effect, where Satisfaction has the greatest effect. However, it did not find the effect of Perceived Value on Loyalty. The conclusion of these findings suggests that good Perceived Value and Brand Equity for higher education products or services will increase Satisfaction, and therefore will have implications for the realisation of increased student Loyalty.